Improving Arterial Blood Gas Collection Skills in Students with SGA Electrical Phantom at Kusuma Husada University, Surakarta - Saputro, Sutiyo Dani; Afni, Anissa Cindy Nurul; Rosida, Nikma Alfi; Barros, Carmelita (IJCS: International Journal of Community Service, 2024)
Diagnostic examination using arterial blood gas can be used as a predictor of the cardiopulmonary condition of patients with critical conditions. Having a rapid diagnostic examination will speed up the treatment provided so that the patient survival rate will increase. GDA taking skills need to be trained and require adequate equipment so that researchers make community service with the aim of improving arterial blood gas taking skills in students using SGA Electrical Phantom at Kusuma Husada University, Surakarta. The service design uses Participatory Action Research (PAR) by involving students in carrying out GDA taking skills before and after using the SGA Electrical Phantom. Community Service was carried out at Kusuma Husada University, Surakarta, involving all final semester students with a sample size of 81 people in the Nursing Study Program. Data analysis used the Wilcoxon test. The results of community service show that there is a significant increase in teenagers' skills in BHD with an average value of 70.12 to 83.08 and the Wilcoxon test results obtained a p value of 0.0001